Climate adaptation through rice northward expansion aggravated groundwater overexploitation in Northeast China - Liang, Shefang; Liu, Weipo; Lu, Miao; Xia, Lang; You, Liangzhi; Liu, Yuan; Liu, Zhenhuan; Zha, Yan; Tang, Huajun; Yang, Peng (Springer, 2025)
Understanding crop migration to adapt to climate change is important to achieve food security and sustainable agriculture. Previous researches mainly focus on the impacts of climate change on crop yields and migration, but environmental feedback has been overlooked. Here we analyze the rice migration and its impact on water use in Sanjiang Plain, Northeast China—which experienced considerable poleward expansion and climate warming. From 2000 to 2020, rice cultivation expanded northeast by 2.19 million hectares, increasing irrigation demand by 6.36 billion tonnes. Rice expansion contributed 122.18% to the abrupt irrigation increase, while the direct impact of climate change resulted in a −22.18% increase due to decreased evapotranspiration and increased precipitation. Such phenomenal rice expansion is considerably associated with the decline of groundwater levels by an average of 4.79 meters. Our findings highlight the urgent need to make integrated strategies balancing crop migration to climate change and water resource conservation.